2022
DOI: 10.1186/s40104-021-00652-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium requirements of broilers fed a conventional corn-soybean meal diet from 1 to 21 days of age

Abstract: Background The current calcium (Ca) recommendation for broilers is primarily based on studies conducted more than 30 years ago with birds of markedly different productive potentials from those which exist today. And the response indicators in these studies are mainly growth performance and bone ash percentage. Therefore, the present study was carried out to investigate the effect of dietary Ca level on growth performance, serum parameters, bone characteristics and Ca metabolism-related gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
4
13
0
Order By: Relevance
“…The CONTRAST statement was utilized for linear and quadratic trend analysis to assess the effects of the CSB supplementation dose on the different parameters. Furthermore, broken-line, asymptotic, and quadratic model regression was carried out using the nonlinear ( NLIN ) procedure of SAS, and the best-fitted model was chosen according to the coefficient of determination and P -value ( Bai et al, 2022 ). The results were displayed in the form of the means and standard error of means, where P < 0.05 indicates the statistical significance and 0.05 ≤ P < 0.1, the statistical trend.…”
Section: Methodsmentioning
confidence: 99%
“…The CONTRAST statement was utilized for linear and quadratic trend analysis to assess the effects of the CSB supplementation dose on the different parameters. Furthermore, broken-line, asymptotic, and quadratic model regression was carried out using the nonlinear ( NLIN ) procedure of SAS, and the best-fitted model was chosen according to the coefficient of determination and P -value ( Bai et al, 2022 ). The results were displayed in the form of the means and standard error of means, where P < 0.05 indicates the statistical significance and 0.05 ≤ P < 0.1, the statistical trend.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the SBL assumes additional supplementation of the nutrient at concentrations above the break point or plateau has no negative impacts on growth performance or nutrient utilization. This may be the case for some nutrients, but high concentrations of total dietary Ca have been shown to reduce growth performance ( Amerah et al., 2014 ; Bai et al., 2022 ; Simco and Stephenson, 1961 ) and P and amino acid digestibility ( Amerah et al., 2014 ) of broilers, especially when dietary P is limiting. Therefore, use of the SBL may over-simplify the effect of dietary Ca on broiler performance, efficiency, and nutrient utilization.…”
Section: Discussionmentioning
confidence: 99%
“… Driver et al. (2005b) and Bai et al. (2022) estimated the requirement to maximize body weight gain (BWG) during the starter phase was 0.625% or 0.590% total Ca, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that dairy cattle make efficient use of calcium and the results showed that both ripe and unripe peels are sufficient to meet the daily calcium needs of cattle. On the other hand, Bai et al (2022) and Poultry Hub (2022) reported 0.59% and 1% as the required calcium need for broiler chickens, hence other calcium sources have to be considered for poultry in addition to the peels of Carica papaya.…”
Section: Proximate and Mineral Composition Of Ripe Carica Papaya Frui...mentioning
confidence: 99%